Emergence of the Anti-Kemalist Movement in the South Marmara: Governor of Izmit Çule Ibrahim Hakkı Bey and the Circassian Congress. Issue 1 (2nd January 2020) - Yelbaşı, Caner
ABSTRACT: The civil war between the Ankara and Ottoman governments between 1920 and 1921 deepened the split among bureaucrats and the military, the two parties supporting the rival governments. After attaining military power, Ankara expanded its control almost to Istanbul, arresting or coercing those statesman who had previously sided with the Ottoman government. The Governor of İzmit, Çule İbrahim Hakkı Bey, was one of these. His activities over a few short years completely altered Ankara's policy towards the Circassians of the South Marmara region. His aim was to establish a society based on the self-determination rights espoused under Wilsonian Principles, to enable the Circassians to elevate their national aspirations. This article firstly examines the motivations of the anti-nationalist Circassians, particularly discussing the activities of Çule İbrahim Hakkı Bey. Secondly it demonstrates how the anti-nationalists established an association, sought foreign support and declared their independence from both the nationalist government of Ankara and the Ottoman government of Istanbul.